Pendidikan Karakter di Era Globalisasi SDN Grujukan 1 - Candra Iliyas Ramadani; Moch. Faron Zainul Abidin; Anggy Sisca Aprilia; Muhammad Ilham Choiron; Nur Alisa Fauziyeh; Setiyono Setiyono; Oria Alit Farisi; Agung Nugroho Puspito (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
Education is a fundamental component in national development, especially for developing countries such as Indonesia, which requires a high-quality next generation. The government has implemented a 12-year compulsory education policy covering education from elementary school (SD) to senior high school (SMA). Elementary school serves as the foundation for early learning for students. Academic education alone is not sufficient to develop a high-quality generation; character education also plays a role in shaping individual attitudes. This social project aims to examine the influence of globalization on the character of children at the elementary school level, as well as to identify character and ethical values associated with the development of globalization. This research was conducted on 4th, 5th, and 6th grade students at SDN Grujukan 1, using practical methods and an ice-breaking approach. This method aims to raise students' awareness of the importance of ethics and character in their daily lives, as well as their responsibilities as learners. The material presented is expected to be applied by students in the future.